Education on the benefits of Indonesian plants as raw materials for herbal cosmetics - Elsa Fitria Apriani; Adik Ahmadi; Vitri Agustiarini; Dwi Hardestyariki; Kamila Alawiyah (Community Empowerment, 2023)
Empowering Tanjung Pering Village people to use local natural resources for herbal cosmetics is important. Cosmetics are now essential, thus their safety from harmful substances must be examined. Using Indonesian herbs may avoid unexpected adverse effects. This program educates Tanjung Pering Village people on using Indonesian herbs for cosmetics using digital books. Implementation involves pre-test, material-provided and post-test. This program gathered 35 Tanjung Pering Village people. Participants receive personal guidance and digital materials to use. Participants' understanding of Indonesian herbs as cosmetic raw materials improved from 51.8% to 94.6% between pretest and posttest. These data show that the program was successful and that public knowledge increased following education.